Firm-Level Determinants of Agency Channel Performance in Indonesia’s Life Insurance Industry - Serpina, Nada; Hafidh, Ezra Pradipta; Melati, Rosi (The International Journal of Financial Systems, 2025)
The insurance sector plays a crucial role in supporting economic stability and household financial protection. However, insurance penetration in Indonesia remains significantly lower than in many peer countries. Improving insurance premium growth is therefore essential, and the agency distribution channel represents one of the key contributors to this objective. This study identifies the key determinants influencing agency channel performance in Indonesia’s life insurance industry, focusing specifically on firm-level factors and their implications for premium growth and market penetration. Using panel data from life insurance companies over the period 2018–2024, a random effects regression analysis reveals significant positive impacts from company total assets, acquisition costs, training costs, number of branch offices, and agent productivity. Affiliation with banking groups, while statistically significant, shows a negative association. Meanwhile, the number of agents, marketing expenses, ownership type, and external macroeconomic factors, including financial sector development indicators, showed no significant influence. These results suggest that internal company resources, structured incentive schemes, well-designed training programs, and expanded branch offices networks are vital for enhancing agency productivity and driving premium growth. The findings emphasise quality over quantity in agency management and suggest targeted strategies for improving distribution effectiveness. From a policy perspective, regulatory authorities such as Otoritas Jasa Keuangan (OJK) should encourage agency professionalisation and closely monitor incentive systems to improve distribution effectiveness and expand insurance penetration. By doing so, the life insurance sector can enhance household financial protection, support financial inclusion, and contribute more effectively to Indonesia’s long-term economic growth.